Markers of Systemic Inflammation in Neuroendocrine Tumors: A Pooled Analysis of the RADIANT-3 and RADIANT-4 Studies. Issue 2 (February 2021) - Chan, David L.; Yao, James C.; Carnaghi, Carlo; Buzzoni, Roberto; Herbst, Fabian; Ridolfi, Antonia; Strosberg, Jonathan; Kulke, Matthew H.; Pavel, Marianne; Singh, Simron
Abstract : Objective: The aim of the study was to assess the impact of systemic markers of inflammation on the outcomes in patients with neuroendocrine tumors (NETs) treated with everolimus or placebo (as measured by baseline neutrophil-to-lymphocyte ratio [NLR] and lymphocyte-to-monocyte ratio [LMR]). Methods: Patient data (gastrointestinal, pancreatic, and lung NETs) from 2 large phase 3 studies, RADIANT-3 (n = 410) and RADIANT-4 (n = 302), were pooled and analyzed. The primary end point was centrally assessed progression-free survival (PFS) as estimated by the Kaplan-Meier method. Results: In the pooled population, elevated LMR (median PFS, 11.1 months; 95% confidence interval, 9.3–13.7; hazard ratio, 0.69; P < 0.001) and reduced NLR (median PFS, 10.8 months; 95% confidence interval, 9.2–11.7; hazard ratio, 0.75; P = 0.0060) correlated with longer PFS among all patients. These markers were also found to be prognostic in the everolimus- and placebo-treated subgroups. Conclusions: Data from this study suggest that LMR and NLR are robust prognostic markers for NETs and could potentially be used to identify patients who may receive or are receiving the most benefit from targeted therapies. As both are derived from a complete blood count, they can be routinely used in clinical practice, providing valuable information to clinicians and patients alike. Abstract : Supplemental digital content is available in the text.